Canaloplasty: Current Value in the Management of Glaucoma - Carlo Cagini; Claudia Peruzzi; Tito Fiore; Leopoldo Spadea; Myrta Lippera; Stefano Lippera (Journal of Ophthalmology)
Canaloplasty is a nonpenetrating blebless surgical technique for open-angle glaucoma, in which a flexible microcatheter is inserted within Schlemm’s canal for the entire 360 degrees. When the microcatheter exits the opposite end, a 10-0 prolene suture is tied and it is then withdrawn, by pulling microcatheter back through the canal in the opposite direction. Ligation of prolene suture provides tension on the canal and facilitates aqueous outflow. The main advantage of canaloplasty is that this technique avoids the major complications of fistulating surgery related to blebs and hypotony. Currently, canaloplasty is performed in glaucoma patients with early to moderate disease and combination with cataract surgery is a suitable option in patients with clinically significant lens opacities.